Síntese de derivados ftalocianínicos de alta conjugação : estratégias envolvendo acoplamentos organometálicos e metano[10]anulenos - Gobo, Nicholas Roberto da Silva (2017)
In this study, the synthesis of phthalocyanine derivatives with extended conjugation were proposed. In order to obtain these compounds, two main strategies were applied. One of them, was the Heck-Mizoroki cross-coupling methodology for the synthesis of substituted naphthalocyanines starting from an octahalogenated phthalocyanine. The other one, was to synthesize a novel phthalocyanine derivative starting from 3,4-dicyano-1,6-methano[10]annulene, which under cyclotetramerization conditions furnished a compound with absorptions at 720 and 800 nm.